A New Perspective on the Role of A‐Site Cations in Perovskite Solar Cells. Issue 14 (22nd January 2018) - Myung, Chang Woo; Yun, Jeonghun; Lee, Geunsik; Kim, Kwang S.
Abstract: As the race toward higher efficiency for inorganic/organic hybrid perovskite solar cells (PSCs) is becoming highly competitive, a design scheme to maximize carrier transport toward higher power efficiency has been urgently demanded. In this study, a hidden role of A‐site cations of PSCs in carrier transport, which has been largely neglected is unraveled, i.e., tuning the Fröhlich electron–phonon (e–ph) coupling of longitudinal optical (LO) phonon by A‐site cations. The key for steering Fröhlich polaron is to control the interaction strength and the number of proton (or lithium) coordination to halide ions. The coordination to I − alleviates electron–phonon scattering by either decreasing the Born effective charge or absorbing the LO motion of I. This novel principle discloses low electron–phonon coupling in several promising organic cations including hydroxyl–ammonium cation (NH3 OH + ), hydrazinium cation (NH3 NH2 + ) and possibly Li + solvating methylamine (Li + ∙∙∙NH2 CH3 ), on a par with methyl–ammonium cations. A new perspective on the role of A‐site cations could help in improving power efficiency and accelerating the application of PSCs. Abstract : A hidden role of A‐site cations in perovskite solar cells in steering Fröhlich polaron coupling is disclosed. Design principles suggest that A‐site cations need to be close to halides and to maximize the coordination to halides. Based on first principles and many‐body theory, organic cations such as NH3 OH +, LiNH2 CH3 +, and NH3 F + are predicted to be promising.